Influence of Service Quality on Word of Mouth Mediated by Tourist Satisfaction at the Budo Tourism Village Homestay - Ukus, Flaura Widya; Sihombing, Irene Hanna H.; Utama, I Putu; Arrey, Mbaze-Ebock Vivian (Jurnal Mamangan, 2024)
In 2022, tourist visits to the Budo Tourism Village were recorded at 64.000 visitors. This figure exceeds the initial target of the village government and Village-Owned Enterprise Management. However, the large number of tourist visits to Budo Village did not increase the number of guests staying at Budo Village homestays. The limited marketing budget from the government and the village-owned enterprise (Bumdes) as managers makes WOM (word of mouth) as the main promotional strategy for homestay managers in the Budo Tourism Village. Another phenomenon encountered is dissatisfaction of guests who stay overnight due to the quality of service received. The above phenomena are related to the theories of service quality, tourist satisfaction, and word of mouth, and are then examined in more depth regarding the influence of service quality on word of mouth mediated by tourist satisfaction. This type of research is quantitative with data collection techniques using a questionnaire created in the form of a GoogleForm and distributed to 174 respondents who have stayed at nine homestays in the Budo Tourism Village. SEM PLS and SPSS analysis were employed to analyze the data. This research found that service quality has a positive and significant influence on tourist satisfaction and Word of Mouth (WOM). Tourist satisfaction has a positive and significant influence on Word of Mouth (WOM) and is also able to mediate the influence of Service Quality on Word of Mouth (WOM). Homestay managers are advised to concern to service quality, such as tidiness and cleanliness, as well as improving internet networks and the availability of free WiFi. Further research will explore the possibility of developing it not only in homestays but also in cafes, restaurants, and even diving centers.